(untitled) (Journal of the College of Basic Education, 2022)
In our present time, the need is increasing day by day to apply scientific thought and modern and technical educational methods in designing educational plans and programs, and the development of the concept of educational design as a result of its use in art education and handicrafts, which includes a range of different skill topics, including what is related to the use of leather material to implement artistic works different. The current research aims to: